2019
DOI: 10.1063/1.5094728
|View full text |Cite
|
Sign up to set email alerts
|

Fourier single-pixel imaging in the terahertz regime

Abstract: We demonstrate Fourier single-pixel imaging in the terahertz regime. The experimental system is implemented with a photo-induced coded aperture setup, where a monolayer graphene on a high-resistance silicon substrate illuminated by a coded laser beam works as a terahertz modulator. Results show that high-quality terahertz images can be reconstructed using greatly reduced number of measurements. We further find that deep photo-induced terahertz modulation by adding a monolayer graphene on the silicon substrate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 45 publications
(31 reference statements)
0
13
0
Order By: Relevance
“…Other recent studies include demonstrating a spinning disc system working from 3 to 13 THz using random masks [45]. Reference [94] shows how random, Hadamard and masks based on the discrete cosine transform perform in the THz regime and reference [95] studied Hadamard vs. Fourier masks in the context of undersampling performance.…”
Section: Applications and Discussionmentioning
confidence: 99%
“…Other recent studies include demonstrating a spinning disc system working from 3 to 13 THz using random masks [45]. Reference [94] shows how random, Hadamard and masks based on the discrete cosine transform perform in the THz regime and reference [95] studied Hadamard vs. Fourier masks in the context of undersampling performance.…”
Section: Applications and Discussionmentioning
confidence: 99%
“…In the THz regime, spatial modulation based on the Fourier and Hadamard basis is commonly adopted with high noise robustness. For instance, She et al reported Fourier single-pixel imaging with high signal-to-noise (SNR) ratio more prominent than 6 . Similarly, the Hadamard mask design, primarily used for THz imaging, represents outstanding SNR as the Fourier mask while containing binary nature.…”
Section: Efficient Subwavelength Terahertz Imaging Techniquesmentioning
confidence: 99%
“…For instance, She et al reported Fourier single-pixel imaging with high signalto-noise (SNR) ratio more prominent than 6. 49 Similarly, the Hadamard mask design, primarily used for THz imaging, represents outstanding SNR as the Fourier mask while containing binary nature. Hadamard matrices have elements whose values are either +1 or −1, and every row is orthogonal to each other.…”
mentioning
confidence: 99%
“…The aim of this study, targeting far-field imaging implementations, was to show how the IFD allows correcting the effect of diffraction when the patterned THz beam propagates for a certain distance before interrogating the sample. Another recent work 53 demonstrated the possibility of realizing and using "Fourier pattern" sets at THz frequencies. In this study, a silicon plate covered with a graphene monolayer was used as a photo-modulator, while the patterning source was a CW laser.…”
Section: All-optical Free-carrier-based Modulatorsmentioning
confidence: 99%